'Back to the Rough Ground!' A Grammatical Approach to Trust and International Relations. (September 2015) - Considine, Laura
This paper asks what it is that we are doing when we talk about trust in international politics. It begins by reviewing the recent and growing body of research on trust and International Relations (IR). It claims that the existing literature is based on particular practices of representation that unquestioningly attempt to find the correct meaning for trust and that this representational account of meaning limits the form of the research, carrying assumptions about meaning that lead to several semantic and methodological problems. The paper challenges this way of understanding through the use of Ludwig Wittgenstein's Philosophical Investigations and proposes an alternative, grammatical approach to trust and IR based on 'meaning as use'. To illustrate this, the paper then conducts a grammatical investigation of the use of trust regarding nuclear arms control with the Soviet Union during the second term of the Reagan presidency. This challenges the familiar narrative of the role of trust at this time by going back to the 'rough ground' of President Reagan's speech on trust and nuclear weapons.